Molecular Identification of Sweet potato virus C on Sweetpotato in Bali, Indonesia - Listihani Listihani; Dewa Gede Wiryangga Selangga (Universitas Gadjah Mada, 2021)
A survey was conducted in several sweet potato cultivations in Bali Province. Survey found that many plants exhibited potyvirus symptom, such as chlorosis blotches. This study was to determine disease incidence, detection and identification of the virus causing these symptoms on sweet potato plants in Bali. Samples were collected by purposive sampling of 10 plants from each location in Bali (Denpasar, Gianyar, Badung, Buleleng, Tabanan, Klungkung, Karangasem, Jembrana, Bangli). Disease insidence was observed based on viral symptoms in the field. Identification of nucleic acids was done using Potyvirus universal primer and DNA sequencing. Disease incidence in Bangli, Buleleng, and Denpasar Regencies was > 50%. RT-PCR and CiFor/CiRev Potyvirus universal primers successfully amplified ± 700 bp of CI genes from all samples from Bangli, while samples from 8 other districts were not amplified using the same primers. The SPVC isolate of sweet potato showed nucleotide and amino acid homology similarities with the sweet potato isolate from East Timor (MF572066), 96.8% and 97.4%, respectively and these were referred to the